FIELD TECTONOPHYSICS IN SOLUTIONS OF GEODYNAMIC EVOLUTION PROBLEMS OF THE UKRAINE TERRITORY - O. B. Gintov; A. V. Murovskaya; S. V. Mychak (Геодинамика и тектонофизика, 2015)
The integrated approach combining kinematic and structural-paragenetic field tectonophysics techniques allows us to construct a continuous time scan of the stress-strain state (SSS) and deformation modes (DM) from sediment lithification to the final orogenic process for the studied areas. Definitions of the continuous sequence of SSS and DM provide for control of the known geodynamic reconstructions and adjustment of geodynamic models. An example is the tectonophysical study of the Alpine structural stage of the Western Mountainous Crimea (WMC) and the Pre-Cambrian complexes of the Ukrainian Shield (USh).Data from WMC allow us to make adjustments to the geodynamic model of the Mountainous Crimea. In particular, trajectories of the principal normal stresses (Fig. 4 and 5), both for shifts and shear faults with reverse components/ normal faults, suggest the reverse nature of movements of the Eastern and Western Black Sea microplates with their overall pushing onto the Crimean peninsula in the south-east, south and south-west (Fig. 7). In the Precambrian USh complexes (Fig. 8), 13 stages of regional deformation are revealed between ≥2.7 and 1.6 billion years ago. Until the turn of 2.05–2.10 billion years, the region was subject to transtension and transpression, as the Western (gneiss-granulite) and Eastern (granite-greenstone) Archean microplates of USh moved to separate from each other in the Neo-Archean and then diverged and converged in the Paleoproterozoic (movements at a sharp angle). It is assumed that in the Archean the Western and Eastern microplates were separated by the oceanic or sub-oceanic lithosphere (Fig. 12, 13). During the period of 2.3–2.4 billion years, the plates fully converged creating a zone of collision. It may be suggested that a possible mechanism for the oceanic window close-up was underthrusting of the upper suboceanic lithosphere layers beneath the crust-mantle plates on gently sloping break-up surfaces (non-subduction option), and one of them is Moho.Spreading of the Western and Eastern microplates of USh began at the turn of 2.05–2.10 billion years, as evidenced by the available tectonophysical data on fields of latitudinal extension of the crust. During spreading 2.1–2.05 billion years ago, emanations and solutions were able to ascend into the upper crust and thus stimulate palingenesis (Novoukrainsky and Kirovogradsky granites), and during repeated spreading 1.75 billion years ago, magma of the basic and acid composition (Pluto gabbro-anorthosite and rapakivi) intruded into the upper crust. The spreading zone coincided with the former collisional suture and became the site wherein the inter-regional Kherson-Smolensk suture was formed; it stretches submeridionally across the East European platform.